Balancing employee flexibility and organizational performance: implications for innovation, productivity, and company attractiveness in SMEs - Eng, Ingela; Aboagye, Emmanuel; Bergsten, Eva L.; Strömberg, Annika (Frontiers in Psychology, 2025)
IntroductionFlexible Work Arrangements (FWA) have become increasingly prevalent, offering employees flexibility in time, tasks, and location. While extensively researched at the employee level, FWAs organizational impact, particularly on innovation, productivity, and perceived organizational attractiveness, is less explored, especially in small and medium-sized enterprises (SMEs). This study aims to explore how FWAs influence these key areas from the perspective of SME managers.MethodA qualitative study used semi-structured interviews with 17 managers from SMEs in Sweden. Participants were selected based on diversity in industry, gender, and experience. Data were analyzed using thematic analysis to identify recurring themes regarding innovation, productivity, and company attractiveness in relation to FWA.ResultsThe results revealed that while FWAs can enhance innovation by promoting employee autonomy and diverse work settings, they may also hinder long-term innovation by reducing spontaneous discussions and collaboration. FWAs may improve individual performance but pose challenges to productivity in coordinating teams and maintaining project timelines, necessitating increased managerial oversight. Additionally, while offering an FWA attracts employees, it may weaken employee loyalty.Discussion/conclusionThese findings highlight the need for SMEs to carefully balance the benefits of FWAs with potential drawbacks, to maintain a competitive edge, suggesting the importance of structured management processes, regulated onsite workdays, and strategies to strengthen organizational connections. This balance is essential for sustaining innovation, productivity, and organizational cohesion. The findings also underscore the complexity of implementing FWAs in a way that supports long-term organizational success.